Mutual control of electric and magnetic orders near room temperature in Al doped Y-type hexaferrite single crystals - Pengzheng Li; Mengfang Yu; Lin Yang; Qiutian Duan; Yinchen Wu; Aihua Zhang; Min Zeng; Meifeng Liu; Xingsen Gao (Journal of Materiomics)
Realizing robust magnetoelectric (ME) coupling effect near room temperature is still a long-standing challenge for the application of multiferroic materials in next-generation low-power spintronic and memory devices. Here we report a systematic study on the magnetic, dielectric, and ME coupling properties of Y-type hexaferrite Ba0.5Sr1.5Co2Fe12–xAlxO22 (x = 0.0, 0.5, 1.0) single crystals. The Al doping can induce the shifting of the alternating longitudinal conical (ALC)-proper screw (PS) magnetic phase transition temperature from 200 K for x = 0–365 K for x = 1.0. The most interesting feature is that the Ba0.5Sr1.5Co2Fe11AlO22 single crystal displays a direct and converse ME coupling coefficient with αH ∼3,100 ps/m and αE ∼3,900 ps/m at 250 K, respectively, due to the Al-doped enhanced stability of ALC phase. Moreover, the exchange bias also verifies the strong coupling of electric and magnetic orders. These results provide a valuable insight on the modulation of ALC structure and the mechanism of ME effect in Y-type hexaferrites.